Explicating the effects of in- versus out-group membership and collective action framing on social media activism messages - Lou, Chen (2024)
Social media activism is a relatively recent phenomenon that has taken off worldwide, where many have taken to social media platforms to relay messages on sociopolitical issues such as racism. However, factors that influence the effects of such activism messages are yet to be studied. This research seeks to address this gap. Informed by selfcategorization theory (SCT) and collective action framing, we conducted an online experiment to test how group membership (in-group vs. out-group) and message framing (diagnostic vs. motivational) affect individuals’ responses to social media activism messages. We found that activism messages promoted by out-group members with a motivational frame (vs. a diagnostic frame) led to greater perceived persuasiveness of the message, whereas activism messages promoted by in-group members revealed no such difference, regardless of the use of frames. The findings promise theoretical contributions to SCT and framing literature and provide insights on using social media to effectively deliver activism messages.